Preparation method and application of water-soluble conductive polyaniline

CN118994571BActive Publication Date: 2026-10-23UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411213447.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2026-10-23
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

然而,目前大多数针对聚苯胺溶液加工法制备电致变色材料的报道主要集中于聚苯胺主链上接枝亲水性聚合物,或者以亲水性聚合物/纳米粒子为模板原位合成聚苯胺,而该方法制备过程麻烦且成本较高

Benefits of technology

[0027]本发明利用旋涂、刮涂、喷涂等技术对上述改性聚苯胺水溶液进行加工,制备柔性大面积和图案化电致变色膜,以PEDOT为对电极,组装出具备高光学对比度高、快速响应时间、优异循环稳定性的电致变色器件,具有广阔的应用前景,有望产生巨大的社会价值和经济价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994571B_ABST
    Figure CN118994571B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of water-soluble conductive polyaniline and application thereof. NMP is introduced into an aniline polymerization system, polyaniline is synthesized by taking NMP / H2O as a mixed solvent, and the molecular weight of the polyaniline is regulated, and then sodium bisulfite or sodium sulfite is taken as a sulfonating agent to perform hydrophilic modification on the polyaniline. The method has the advantages of simple preparation, mild conditions and no need of a template, and the modified product has water solubility and electrical conductivity, can be used for preparation of a large-area flexible electrochromic film, and has practical guiding significance for industrialized production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional polymers, specifically relating to a method for preparing water-soluble conductive polyaniline and its application. Background Technology

[0002] Polyaniline (PANI), as one of the three major conductive polymers, exhibits excellent thermal stability at temperatures up to 250°C and can be easily synthesized through chemical oxidative polymerization and electrochemical methods. Furthermore, due to its low cost, excellent environmental stability, and good electrical conductivity, PANI has attracted considerable attention in fields such as electrochromism, electromagnetic interference shielding, solar cells, bio / chemical sensors, and corrosion protection, offering irreplaceable advantages compared to polypyrrole and polythiophene. However, due to its rigid backbone and strong π-π stacking and hydrogen bonding between chains, PANI lacks solution processability and is only soluble in a very few specific organic solvents, such as NMP, DMF, and DMSO. These organic solvents have boiling points exceeding 150°C, with NMP even exceeding 200°C. These high-boiling-point solvents are difficult to remove after processing and generally possess a certain degree of toxicity. Therefore, improving the hydrophilicity of PANI is the optimal strategy to enhance its processability. To achieve this strategy, researchers have done a lot of work, and there are currently two main methods: (1) attaching hydrophilic sulfonic acid groups to the polyaniline backbone. Usually, sulfonation of polyaniline is carried out with fuming sulfuric acid or chlorosulfonic acid, which can greatly improve the water solubility of polyaniline. Yue et al. dissolved polyaniline emerald base in fuming sulfuric acid and prepared sulfonated polyaniline with an S / N ratio of up to 0.5, but the product can only be dissolved in sodium hydroxide or ammonia water, which loses its practical application value (J. Am. Chem. Soc. 1990, 112, 7, 2800-2801). Shoji Ito et al. sulfonated polyaniline with chlorosulfonic acid. When the degree of sulfonation (S / N) was 0.65, the product solubility was 22 mg / mL and the conductivity was 0.028 S / cm. When the degree of sulfonation was 0.80, the product solubility was 51 mg / mL and the conductivity was 5.72 × 10 -3S / cm (Synthetic Metals 1998, 96, 161-163). It can be seen that the improvement in water solubility of the product by this method comes at the cost of electrical conductivity. Moreover, fuming sulfuric acid and chlorosulfonic acid are extremely dangerous and not conducive to practical production applications. Another method is to copolymerize aniline and m-aminobenzenesulfonic acid (MA). The disadvantage is that the different reactivity of the two monomers can easily lead to uneven copolymer segments, and the product can only be dissolved in alkaline aqueous solution (Journal of Polymer Science Part A: Polymer Chemistry 2000, 38, 3390-3398). (2) Grafting hydrophilic polymers onto the polyaniline backbone, or synthesizing polyaniline in situ using hydrophilic polymers / nanoparticles as templates. Du et al. polymerized aniline in situ in the presence of chitosan, grafting chitosan onto the polyaniline chains to enable dispersion in water. This was then combined with acrylamide monomers to synthesize Chi-g-polyaniline-polyacrylamide hydrogels (ACS Appl. Mater. Interfaces 2023, 15, 23711-23724). Lü et al. used poly(2-acrylamide-2-methylpropanesulfonic acid) (PAMPS) as a doping acid and emulsifier, utilizing its unique long-chain, hydrophilic, and strongly acidic group effects to synthesize highly soluble conductive polyaniline in one step via emulsion polymerization. The polyaniline obtained by this method is water-soluble and has high conductivity, and the reagents used are not hazardous. However, it requires the introduction of other polymers, making the preparation method cumbersome and costly. In summary, current methods for hydrophilic modification of polyaniline all have corresponding drawbacks. Therefore, finding a simple and low-cost method for hydrophilic modification of polyaniline is essential.

[0003] Electrochromic materials can stably and reversibly change their optical properties under an applied electric field, showing significant application potential in energy-saving windows, smart displays, and military camouflage. Polyaniline, due to its simple preparation, low cost, rich color changes, and fast response time, has become a widely studied conductive polymer electrochromic material. The color change of polyaniline within an application potential range of ±1V is closely related to the changes in its absorption spectrum in the visible light range (400-800 nm). The correlation between the electrochromic properties of polyaniline and visible light transmission has led to the development of electrochromic displays and windows combined with complementary electrochromic materials.

[0004] Currently, the main methods for preparing polyaniline electrochromic materials include electropolymerization, enzymatic synthesis, and solution processing (spin coating, blade coating, spray coating, etc.). For electropolymerization, the deposition of polyaniline is affected by current density and electrode surface conditions, making it difficult to precisely control film thickness and uniformity, resulting in poor reproducibility and hindering large-scale production. Enzymatic synthesis suffers from drawbacks such as expensive enzymes, sensitivity to storage conditions, limited reaction conditions, and difficulty in large-scale production. Solution processing, due to its good reproducibility, excellent coating uniformity, and suitability for large-scale production, has become the preferred strategy for preparing polyaniline electrochromic layers. The implementation of solution processing requires hydrophilic modification of polyaniline. However, most current reports on the preparation of electrochromic materials using polyaniline solution processing focus on grafting hydrophilic polymers onto the polyaniline backbone or synthesizing polyaniline in situ using hydrophilic polymers / nanoparticles as templates. These methods are cumbersome and costly. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a method for preparing water-soluble conductive polyaniline and its applications. This invention introduces NMP into the aniline polymerization system, specifically using NMP / H2O as a mixed solvent to synthesize polyaniline to control its molecular weight. Then, sodium bisulfite or sodium sulfite is used as a sulfonating agent to hydrophilically modify the polyaniline. This method is simple, operates under mild conditions, requires no template, and produces a modified product that combines water solubility and electrical conductivity. It can be used to prepare large-area flexible electrochromic films, providing practical guidance for industrial production applications.

[0006] The method for preparing water-soluble conductive polyaniline of the present invention includes the following steps: Step 1: Synthesis of PANI The aniline monomer was dissolved in a NMP / H2O mixed solvent and stirred in an ice-water bath at 0°C for 10 minutes. The ammonium persulfate (APS) solid was dissolved in hydrochloric acid and then added dropwise to the aniline solution. After the addition was complete, the polymerization system was kept at 0°C for one hour. After the reaction was completed, PANI was washed with deionized water and centrifuged. This process was repeated 5 times. After the last wash, the PANI solid was obtained by vacuum filtration.

[0007] Step 2: Synthesis of SPAN Dissolve the PANI obtained in step 1 in a mixed solvent of NMP / H2O and stir to disperse evenly. Dissolve the sulfonating agent in water and add it to the reaction system. React at 60-70℃ for 0.5-2 hours. After the reaction is complete, wash the product SPAN with deionized water and centrifuge. Repeat the operation until the pH of the supernatant is 3-4.

[0008] The volume ratio of NMP to H2O in the NMP / H2O mixed solvent is 1:1 to 1:5.

[0009] The sulfonating agent is a water-soluble bisulfite or sulfite, preferably sodium bisulfite or sodium sulfite.

[0010] The molar ratio of the sulfonating agent to the aniline monomer is 1:1 to 1:5, more preferably 1:2 to 1:4.

[0011] The polyaniline prepared by this invention is a conjugated polymer composed of an oxidized quinone structure and a reduced benzene structure. This invention uses a chemical oxidative polymerization method to prepare polyaniline, with NMP and water as solvents. By adjusting the ratio of these two solvents, polyanilines of different molecular weights can be obtained, ranging from 10,000 to 30,000.

[0012] The method for preparing a flexible electrochromic film using the water-soluble conductive polyaniline includes the following steps: SPAN is dissolved in water, and the supernatant is collected after centrifugation to obtain a SPAN solution. A surfactant is added to the SPAN solution to obtain a coating solution. Then, an SPAN electrochromic film is prepared on an ITO-PET substrate by spin coating, blade coating or spray coating.

[0013] The concentration of the SPAN solution is 3-6 mg / mL.

[0014] The volume ratio of the surfactant to the SPAN solution is 1:15 to 1:25.

[0015] The surfactant includes polyethylene glycol octylphenyl ether (Triton X-100). The purpose of adding the surfactant is to increase the wettability and spreadability of the solution on the ITO-PET substrate.

[0016] The coating solution also includes PVP. The original SPAN solution meets the requirements for spin coating, but its viscosity is too low for spraying and blade coating. Therefore, PVP is added to thicken it, making it suitable for both. Additionally, PVP is polyvinylpyrrolidone; its carbonyl oxygen bonds with the hydrogen atoms on the nitrogen atoms of the SPAN molecular chain, making the molecular chain more extended and stabilizing the SPAN solution.

[0017] An example of the preparation method of SPAN electrochromic film is as follows: The SPAN electrochromic film was prepared by spin coating, and the specific steps are as follows: Dissolve a certain amount of SPAN in water, centrifuge at a certain rate, and collect the supernatant to obtain a SPAN solution with a concentration of 3-6 mg / ml. Add 40-65 μL of Ttiton X-100 to the SPAN solution to obtain the coating solution. Cut ITO-PET into rectangular blocks of 20 mm × 35 mm and place them on the base of a spin coater. Spread a certain amount of the coating solution evenly on the substrate, spin at 700-1000 r / min for 4-6 seconds, heat to dry, and repeat the above spin coating steps 1-8 times to obtain a uniform SPAN electrochromic film.

[0018] The SPAN electrochromic film was prepared using a blade coating method. The specific steps are as follows: Dissolve a certain amount of SPAN in water, centrifuge at a certain rate, and collect the supernatant to achieve a solution concentration of 3-6 mg / ml, thus obtaining the SPAN solution. Add PVP to the SPAN solution, stir to dissolve, and then add 40-65 μL of Triton X-100 solution to the SPAN-PVP solution to obtain the coating solution. Take a certain amount of the coating solution and spread it on one side of a 30mm × 60mm ITO-PET film to form an area of ​​approximately 5mm × 30mm. Use a 50-200 μm wire rod to scrape the solution to the other side, and heat to dry, thus obtaining the SPAN electrochromic film.

[0019] The SPAN electrochromic film was prepared by spray coating, and the specific steps are as follows: Dissolve a certain amount of SPAN in water, centrifuge at a certain rate, and collect the supernatant to achieve a solution concentration of 3-6 mg / ml, thus obtaining the SPAN solution. Add PVP to the SPAN solution, stir to dissolve, and then add an appropriate amount of Triton X-100 solution to the SPAN-PVP solution to obtain the coating solution. Cut ITO-PET into rectangular blocks of 40mm × 60mm size, and place a perforated mask on its surface. Add the coating solution to an airbrush and spray it onto the ITO-PET with the mask attached for 3-5 seconds. Heat and dry the film, then peel off the mask to obtain an electrochromic film with the corresponding pattern.

[0020] The method for preparing an electrochromic device using the flexible electrochromic film includes the following steps: Using the SPAN electrochromic film as the positive electrode and the poly(3,4-ethylenedioxythiophene) (PEDOT) film as the negative electrode, an electrolyte solution (the electrolyte solution formula is: 0.4g LiClO4 added to 12 ml PC, stirred until dissolved, then 3g polymethyl methacrylate added, stirred until dissolved) is injected in the middle. Then the device is placed under a UV lamp for a certain period of time to obtain the SPAN-PEDOT electrochromic device.

[0021] The PEDOT membrane is prepared using the same method as SPAN, that is, by adding an appropriate amount of Triton X-100 to a PEDOT:PSS solution as a coating and preparing the PEDOT membrane using spin coating, blade coating or spray coating methods.

[0022] The PEDOT:PSS solution was commercially available. Specifically, the PEDOT:PSS solution was diluted 5 times, and then 1 ml of the diluted solution was taken and 40-65 μL of Triton-X (the volume ratio of Triton-X to the solution was 1:15-1:25) was added. This solution was used as a coating material to prepare PEDOT films using spin coating, blade coating, or spray coating methods.

[0023] The SPAN-PEDOT electrochromic device of this invention features large optical modulation amplitude, fast response time, and excellent cycle stability.

[0024] The preparation process of sulfonated polyaniline according to this invention consists of two steps: the synthesis of polyaniline and the sulfonation modification of polyaniline. In the first step, polyaniline is synthesized using NMP / H2O as a solvent. Since NMP (N-methylpyrrolidone) is a good solvent for polyaniline, its addition affects the polymerization rate of aniline. Therefore, by controlling the NMP content, polyanilines of different molecular weights can be obtained. In the second step, sodium bisulfite or sodium sulfite is used as a sulfonating agent to sulfonate polyaniline (reaction mechanism as follows). Because the degree of sulfonation, water solubility, and electrical conductivity of polyanilines of different molecular weights vary under different conditions, sulfonated polyaniline (SPAN) with both water solubility and electrical conductivity can be obtained by controlling the conditions for synthesizing and sulfonating polyaniline.

[0025]

[0026] The sulfonation mechanism of sodium bisulfite on polyaniline differs from that of fuming sulfuric acid / chlorosulfonic acid. Sodium bisulfite is a common nucleophile, typically used for nucleophilic addition to the carbonyl groups of aldehydes and ketones. The "C=C" on the quinone ring of polyaniline becomes electron-deficient due to the protonated imine nitrogen atom, thus exhibiting nucleophilic addition activity. Therefore, this invention uses sodium bisulfite or sodium sulfite as a nucleophile to perform nucleophilic addition to the quinone ring of polyaniline, allowing a sulfonic acid group to be incorporated into the polyaniline backbone, improving its water solubility without degrading the polyaniline. This method is simple to prepare, operates under mild conditions, is inexpensive, and requires no other hydrophilic substances.

[0027] This invention utilizes spin coating, blade coating, and spray coating techniques to process the above-mentioned modified polyaniline aqueous solution to prepare a flexible, large-area, and patterned electrochromic film. Using PEDOT as the counter electrode, an electrochromic device with high optical contrast, fast response time, and excellent cycle stability is assembled, which has broad application prospects and is expected to generate huge social and economic value. Attached Figure Description

[0028] Figure 1 XRD patterns of PANI, SPAN (1:2), SPAN (1:3), and SPAN (1:4). After sulfonation, the diffraction peaks of SPAN are not as sharp as those of PANI. This is because the sulfonic acid groups on the PANI molecular chain increase the steric hindrance between chain segments and increase the gaps between chain segments, which reduces the crystallinity of polyaniline and weakens its conjugation.

[0029] Figure 2 FT-IR spectra of PANI, SPAN (1:2), SPAN (1:3), and SPAN (1:4). 1073 and 1019 cm⁻¹ -1 These are the symmetric and asymmetric stretching vibration peaks at O=S=O, respectively, at 704 cm⁻¹. -1 The corresponding SO symmetric stretching vibration peak indicates the successful synthesis of SPAN.

[0030] Figure 3 UV-Vis spectra of PANI, SPAN (1:2), SPAN (1:3), and SPAN (1:4). The two absorption peaks of polyaniline are located near 365 nm and 625 nm, respectively. The absorption peak at 365 nm is the absorption peak of the π-π* electronic transition of the benzene ring, and the absorption peak at 625 nm is the absorption peak of the polaron / bipolaron transition of PANI. Compared with PANI, the peak at 625 nm of SPAN redshifts with increasing sulfonation degree, meaning that the bipolaron / polaron transition becomes easier after sulfonation. This may be due to the additional protonation of the sulfonic acid group, forming a self-doped six-membered stable ring structure, thereby improving the stability of the conjugated system.

[0031] Figure 4 Cyclic voltammetry curves of SPAN films prepared by spin coating in 0.1 mol / L LiClO4 / PC. Voltage range: -0.4 to 1.2 V, scan rate: 0.05 V / s. During the forward scan, two oxidation peaks appear at approximately 0.35 V and approximately 0.9 V, corresponding to the changes between the reduction of polyaniline salt-emerald green imide salt and emerald green imide salt-poly(p-phenyleneimide salt), respectively, with the polyaniline film successively exhibiting yellow-green, green, and blue colors. During the reverse scan, two reduction peaks appear at approximately 0.66 V and approximately 0.07 V, corresponding to the reversible process of the forward scan.

[0032] Figure 5 Color change diagram of SPAN film in LiClO4 / PC. As the voltage changes from -0.4 V to 1.2 V, SPAN undergoes a transformation from yellow-green to green to blue.

[0033] Figure 6(a) Transmittance curves (300-800 nm) of the SPAN film after 6 spin coatings from -0.4 to 1.2 V; (b) Time response curves of the SPAN film. The light modulation amplitude of the SPAN film reaches 44.7% at a wavelength of 684 nm, with a coloring time of 2.7 seconds and a fading time of 2 seconds.

[0034] Figure 7 Color-changing pattern of SPAN-PEDOT devices from -1.2 to 1.4 V. The device is green at low voltage and dark blue-violet at high voltage.

[0035] Figure 8 (a) Transmittance curves of SPAN-PEDOT devices prepared by spin coating in the 300-800 nm range; (b) Time response curves of SPAN-PEDOT devices. The device achieves a light modulation amplitude of 40.1% at 582 nm, with a coloring time of 2.2 seconds and a fading time of 1.8 seconds.

[0036] Figure 9 (a) CV diagrams of the SPAN-PEDOT device at the initial stage and after 1000, 2000, 3000, 4000, and 5000 color-changing cycles; (b) Curves of the cycling stability of the SPAN-PEDOT device tested by the potential step method.

[0037] Figure 10 (a) Transmittance curves of SPAN-PEDOT devices prepared by the blade coating method in the 300-800 nm range; (b) Time response curves of SPAN-PEDOT devices. The device achieves a light modulation amplitude of 39.4% at 582 nm, with a coloring time of 2.5 seconds and a fading time of 2 seconds.

[0038] Figure 11 (a) CV diagrams of the SPAN-PEDOT device at the initial stage and after 1000, 2000, 3000, 4000, and 5000 color-changing cycles; (b) Curves of the cycling stability of the SPAN-PEDOT device tested by the potential step method.

[0039] Figure 12 A large-area (60 mm × 60 mm) SPAN-PEDOT device fabricated using a blade coating method was demonstrated.

[0040] Figure 13 Color change pattern of SPAN-PEDOT patterned electrochromic device prepared by spray coating method. Detailed Implementation

[0041] The technical solution of the present invention will be further analyzed and explained through specific embodiments below.

[0042] Example 1: Synthesis of PANI 1. Dissolve 3.6 g of aniline in 15 ml of NMP and 25 ml of 1 mol / L hydrochloric acid, and stir at 0°C. Dissolve 9.13 g of APS in 20 ml of 1 mol / L hydrochloric acid, and then add the APS solution dropwise to the aniline solution at a rate of 3-5 seconds per drop.

[0043] 2. After the addition is complete, the polymerization system reacts for one hour.

[0044] 3. After the reaction is complete, wash the PANI product with deionized water and centrifuge, repeating the process 5 times. After the final wash, filter to obtain dark green PANI solid.

[0045] Example 2: Sodium bisulfite used in the synthesis of SPAN 1. Disperse the PANI obtained in the previous step in 9 ml NMP and 27 ml water, and stir to make it evenly dispersed.

[0046] 2. Dissolve 2.08 g of sodium bisulfite in 6 ml of water (the molar ratio of sodium bisulfite to aniline monomer in the PANI synthesis step is 1:2), add it to the reaction system, and react at 65°C for 1 h.

[0047] 3. After the reaction is complete, wash the dark green product SPAN with deionized water and centrifuge. Repeat the operation until the pH of the supernatant is 3-4.

[0048] Example 3: Sodium bisulfite used in the synthesis of SPAN 1. Disperse the PANI obtained in the previous step in 9 ml NMP and 27 ml water, and stir until evenly dispersed. Adjust the pH of the reaction system to 2-4 with acetic acid.

[0049] 2. Dissolve 2.52 g of sodium sulfite in 6 ml of water (the molar ratio of sodium sulfite to aniline monomer in the PANI synthesis step is 1:2), add it to the reaction system, and react at 65°C for 1 h.

[0050] 3. After the reaction is complete, wash the dark green product SPAN with deionized water and centrifuge. Repeat the operation until the pH of the supernatant is 3.5.

[0051] Table 1 shows the molecular weight of polyaniline synthesized under different NMP / H2O ratios.

[0052] Table 2 presents the optimal NMP / H2O solvent ratios for the sulfonation of polyaniline synthesized at different NMP / H2O ratios. Each sample exhibits different dispersibility in NMP / H2O due to variations in molecular weight. Since sodium bisulfite is poorly soluble in NMP, the optimal solvent ratio for sulfonation differs for each sample.

[0053] Table 3 presents the degree of sulfonation (S / N), conductivity, and solubility of polyaniline synthesized in different NMP / H2O solvent ratios at different n(sodium bisulfite) / n(ANI) ratios. It can be seen that different molecular weights of polyaniline lead to different conductivity. With increasing NaHSO3 content, the degree of sulfonation and solubility increase, while the conductivity decreases.

[0054]

[0055]

[0056]

[0057] Example 4: Preparation of SPAN film by spin coating 1. Dissolve 1 g of SPAN (1:2) in 5 ml of water, centrifuge at 3000 r / min, and collect the supernatant to obtain the SPAN solution. Add 60 μL of Ttiton X-100 to the SPAN solution to obtain the coating solution.

[0058] 2. Ultrasonically clean the ITO-PET in toluene, acetone, ethanol, and deionized water for 10 minutes each, then dry it. Cut the ITO-PET into rectangular blocks of 20 mm × 35 mm and place them on the base of a spin coater. Spread 1 mL of coating solution evenly on the substrate, spin at 900 rpm for 5 seconds to obtain a uniform SPAN film.

[0059] 3. After drying the SPAN film in a 65℃ oven for a period of time, remove it and repeat the spin coating steps above 6 times.

[0060] Example 5: Assembly of SPAN-PEDOT electrochromic device prepared by spin coating 1. Take 1 ml of PEDOT:PSS solution, add 60 μL of Triton X-100, and then take 50 μL of the coating solution and spread it on ITO-PET. Rotate at 900 r / min for 5 seconds to obtain a uniform PEDOT film.

[0061] 2. Using the SPAN film as the positive electrode and the PEDOT film as the negative electrode, an electrolyte solution is injected in the middle. Then, the device is placed under a UV lamp for 5 minutes to obtain the SPAN-PEDOT electrochromic device.

[0062] Example 6: Preparation of SPAN film by blade coating 1. Dissolve 1 g of SPAN in 5 ml of water, centrifuge at 3000 r / min, and collect the supernatant to obtain the SPAN solution. Add 0.1 g of PVP to 10 ml of SPAN solution and stir to dissolve to obtain the SPAN-PVP solution.

[0063] 2. Add 60 μL of Triton X-100 solution to 1 ml of SPAN-PVP solution. Take 50 μL of the solution and spread it on one side of a 30 mm × 60 mm ITO-PET film to form an area of ​​about 5 mm × 30 mm. Hold a 100 μm wire rod and scrape the solution to the other side. Dry at 65℃ to obtain the SPAN electrochromic film.

[0064] The assembly steps and electrochromic performance testing steps of the SPAN-PEDOT device prepared by the scraping method provided by this invention are the same as those of the spin coating method.

[0065] Example 7: Preparation of SPAN patterned electrochromic film by spray coating 1. Dissolve 1 g of SPAN in 5 ml of water, centrifuge at 3000 r / min, and collect the supernatant to obtain the SPAN solution. Add 0.1 g of PVP to 10 ml of SPAN solution and stir to dissolve to obtain the SPAN-PVP solution.

[0066] 2. Cut the ITO-PET into a rectangular block measuring 40 mm × 60 mm, and attach the perforated mask printed with "EC" to it. Add 300 μL of Triton X-100 solution to 5 ml of SPAN-PVP solution, pour the spraying liquid into the airbrush, and spray the ITO-PET with the mask attached for 4 seconds.

[0067] 3. Dry the film at 65°C. Remove the photomask to obtain an electrochromic film printed with the "EC" pattern.

[0068] A PEDOT patterned electrochromic film was prepared using the same method. The SPAN film and the PEDOT film were then assembled to obtain the patterned electrochromic device.

[0069] The performance testing steps for SPAN flexible electrochromic film are as follows:

[0070] (1) The SPAN membrane was placed in a three-electrode system as the working electrode, with a platinum wire as the counter electrode, Ag / AgCl as the reference electrode, and LiClO4 / propylene carbonate (PC) as the electrolyte. The system was connected to an electrochemical workstation, and cyclic voltammetry was performed within a certain voltage range. The CV curve was recorded.

[0071] (2) Place the entire apparatus in the colorimetric cell of the UV-Vis spectrophotometer, using the blank electrolyte as a reference, and use the voltage step method to test the transmission spectra of the SPAN film in the fading and colored states in the range of 300~800 nm. Find the wavelength corresponding to the maximum transmittance difference in the spectrum, and use this as a single wavelength to test the coloring / fading time of the SPAN film.

[0072] The electrochromic performance testing steps for SPAN-PEDOT devices are as follows:

[0073] The CV curves were recorded using an electrochemical workstation within a certain voltage range; the transmission spectra of the device in the fading and colored states in the 300-800 nm range were recorded using a UV-Vis spectrophotometer, and the coloring / fading time of the device was tested; the cyclic color-changing performance of the SPAN-PEDOT device within a certain voltage range was tested using the step method.

[0074] Table 4 presents the light modulation amplitude and coloring / fading time of SPAN films with different spin-coating times. It can be seen that the SPAN film with 6 spin-coatings has the largest light modulation amplitude.

[0075]

Claims

1. A method for preparing water-soluble conductive polyaniline, characterized in that: Polyaniline was synthesized using NMP / H2O as a mixed solvent to control its molecular weight. Then, the polyaniline was sulfonated and hydrophilically modified to obtain water-soluble conductive polyaniline. Includes the following steps: Step 1: Synthesis of PANI The aniline monomer was dissolved in a NMP / H2O mixed solvent and stirred in an ice-water bath at 0°C for 10 minutes. The ammonium persulfate solid was dissolved in hydrochloric acid and then added dropwise to the aniline solution. After the addition was complete, the polymerization system was kept at 0°C for the reaction. After the reaction was completed, PANI was washed with deionized water, centrifuged, and filtered to obtain PANI solid. Step 2: Synthesis of SPAN Dissolve the PANI obtained in step 1 in a mixed solvent of NMP / H2O and stir to disperse evenly. Dissolve the sulfonating agent in water and add it to the reaction system. React at 60-70℃ for 0.5-2 hours. After the reaction is complete, wash the product SPAN with deionized water and centrifuge. Repeat the operation until the pH of the supernatant is 3-4. The volume ratio of NMP to H2O in the NMP / H2O mixed solvent is 1:1 to 1:5; The sulfonating agent is a water-soluble bisulfite or sulfite.

2. The method for preparing water-soluble conductive polyaniline according to claim 1, characterized in that: The sulfonating agent is sodium bisulfite or sodium sulfite.

3. The method for preparing water-soluble conductive polyaniline according to claim 1, characterized in that: The molar ratio of the sulfonating agent to the aniline monomer is 1:1 to 1:

5.

4. A method for preparing a flexible electrochromic film, characterized in that: Using water-soluble conductive polyaniline obtained by any one of the preparation methods in claims 1-3 as raw material, the process includes the following steps: SPAN is dissolved in water, and the supernatant is collected after centrifugation to obtain a SPAN solution. A surfactant is added to the SPAN solution to obtain a coating solution. Then, an SPAN electrochromic film is prepared on an ITO-PET substrate by spin coating, blade coating or spray coating.

5. The method for preparing the flexible electrochromic film according to claim 4, characterized in that: The concentration of the SPAN solution is 3-6 mg / mL.

6. A method for constructing an electrochromic device, characterized in that: Using the SPAN electrochromic film prepared by the method described in claim 4 or 5 as the positive electrode and the poly(3,4-ethylenedioxythiophene) film as the negative electrode, an electrolyte solution is injected in the middle, and then the device is placed under an ultraviolet lamp for irradiation to obtain the SPAN-PEDOT electrochromic device.

Citation Information

Patent Citations

  • Method for preparing fusible conductive polyaniline

    CN1415645A

  • Sulfonated aliphatic compounds

    US5919976A